ACE: Abstracting, Characterizing and Exploiting Peaks and Valleys in Datacenter Power Consumption - Wang, Di; Ren, Chuangang; Govindan, Sriram; Sivasubramaniam, Anand; Urgaonkar, Bhuvan; Kansal, Aman; Vaid, Kushagra (ACM SIGMETRICS (Posters), 2013)
Peak power management of datacenters has tremendous cost implications. While numerous mechanisms have been proposed to cap power consumption, real datacenter power consumption data is scarce. To address this gap, we collect power demands at multiple spatial and ﬁne-grained temporal resolutions from the load of geo-distributed datacenters of Microsoft over 6 months. We conduct aggregate analysis of this data, to study its statistical properties. With workload characterization a key ingredient for systems design and evaluation, we note the importance of better abstractions for capturing power demands, in the form of peaks and valleys. We identify and characterize attributes for peaks and valleys, and important correlations across these attributes that can inﬂuence the choice and eﬀectiveness of diﬀerent power capping techniques. With the wide scope of exploitability of such characteristics for power provisioning and optimizations, we illustrate its beneﬁts with two speciﬁc case studies.